Stochastic Dynamic Programming - Kjetil Kåre Haugen (Scandinavian University Press (Universitetsforlaget), 2016)
This text gives a comprehensive coverage of how optimization problems involving decisions and uncertainty may be handled by the methodology of Stochastic Dynamic Programming (SDP). A rapidly changing world with seemingly growing uncertainty needs a modern approach to this classic methodology. The book treats discrete, as well as continuous problems, all illustrated by relevant real world examples. The book presents a comprehensive outline of SDP from its roots during World War II until today. Much of recent research are covered, as well as parts of the authors' own original research. Algorithms and computer techniques are added when needed. The book may serve as a supplementary text book on SDP (preferably at the graduate level) given adequate added background material. Kjetil Kåre Haugen is a professor of Logistics and Sport Management at Molde University College, Specialized University in Logistics.